Pemberdayaan Masyarakat Tani melalui Pelatihan dan Pendampingan Budidaya Jagung dengan Metode Tanam Tanpa Olah Tanah (TOT) - Sylvina Rusadi; Panca Setyo Prihatin; Monalisa; Ilma Satriana Dewi; Rosmita; Christine B. Tenorio (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – Food security is a crucial concern that the central government prioritises for the populace. One method to attain food security is by maize cultivation. Nonetheless, inadequate comprehension, techniques, and resources from the community result in agricultural failure. Community empowerment is essential for enhancing partners' comprehension and the quality of their agricultural produce. The aims of this initiative for corn farmer collectives are: firstly, to enhance the group's comprehension of corn cultivation via the No-Tillage (TOT) technique; and secondly, to augment corn yield by supplying fertilisers, high-quality seeds, and technical implements such as mini tractors Design/methodology/approach – The process necessitates many critical steps: outreach, training, technology installation, and subsequent evaluation and monitoring. This method comprises a sequence of activities executed in accordance with the issues and resolutions presented by the community service team. Findings – The findings indicate that this exercise improved the comprehension and proficiency of farmer groups in executing the No-Tillage Planting (TOT) technique in maize agriculture. Farmers enhanced their land management through training, mentoring, and the provision of high-quality seeds, fertilisers, dolomite, and small tractors. The program resulted in an 85% increase in corn harvest yields after its introduction. Originality/value – This training session represents an innovative approach to soil processing for maize cultivation.